A low-heat portland cement special-purpose strength improver, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611242412.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-16
AI Technical Summary
然而,由于LHPC中水化惰性相硅酸二钙(C2S)和铁铝酸四钙(C4AF)的比例较高,LHPC一直面临着早期强度低的问题,这限制了其应用场景,如在寒冷环境下的混凝土修复工程等
本发明针对LHPC矿物相组成的特点,提供了一种可以不增加水化放热量且同时提高LHPC早期和后期强度的外加剂。本发明通过复掺新型纳米复合材料及三元醇胺等物质,在低剂量下可以协同促进LHPC各龄期水化,提升强度,这对于低热硅酸盐水泥进一步推广和实际应用具有重要意义。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of building material admixtures technology, and particularly relates to a low-heat silicate cement-specific strengthening agent, its preparation method and application. Background Technology
[0002] Cement, as the most widely used and consumed building material, plays an irreplaceable role in modern economic and social development. However, due to its high carbon emissions during production, carbon reduction in the cement industry is urgent. To address this, the industry often employs methods such as using supplementary cementitious materials (SCMs), developing and utilizing low-carbon cement, and using CCS technology. However, with the continuous increase in demand for SCMs, their long-term availability will continue to decline. Furthermore, CCS technology is currently not mature enough. Under these circumstances, a mature and feasible approach is to use low-carbon cement. Low-heat silicate cement (LHPC), as a typical representative, has advantages such as low energy consumption, low carbon emissions, and good durability. However, due to the high proportion of hydrated inert phases dicalcium silicate (C2S) and tetracalcium aluminoferrite (C4AF) in LHPC, it has always faced the problem of low early strength, which limits its application scenarios, such as concrete repair projects in cold environments. In recent years, scholars both at home and abroad have conducted numerous studies on improving the early strength of LHPC, mainly focusing on C2S activation. However, these activation methods are complex and costly. Simple and cost-effective activation methods are usually achieved through admixture activation, but the development of admixtures specifically for low-heat silicate cement is very limited in the current technology, especially without increasing the early hydration heat release.
[0003] Therefore, how to provide a simple and cost-controllable low-heat silicate cement admixture is a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention proposes a low-heat silicate cement-specific strengthening agent, its preparation method, and its application.
[0005] To achieve the above objectives, the present invention provides the following technical solution: A low-heat silicate cement strengthening agent includes a liquid strengthening agent and auxiliary powder materials; The mass ratio of the liquid reinforcing agent to the auxiliary powder material is (55-90):(25-30). The liquid strengthening agent comprises the following raw materials in parts by weight: 10-15 parts of triolamine, 25-35 parts of novel nanocomposite material, 5 parts of cyclodextrin, 5 parts of sugar, and 10-30 parts of water.
[0006] Preferably, the triolamine includes triisopropanolamine or diethanol monoisopropanolamine.
[0007] Beneficial effects: The main function of triolamines is to deplete sulfates in advance during the hydration deceleration phase, thereby triggering the rehydration of the aluminate phase (mainly C4AF) and increasing the degree of hydration. However, the rehydration of the aluminate phase inevitably interferes with / inhibits the hydration of the silicate phase. Therefore, the purpose of introducing auxiliary powder materials is, on the one hand, to delay the early interference with C3S hydration, and on the other hand, to reduce the early hydration temperature rise.
[0008] Preferably, the novel nanocomposite material is a nano-hydrated calcium iron silicate / polycarboxylate superplasticizer material (nano-CFSH / PCE).
[0009] Preferably, the preparation method of the novel nanocomposite material includes the following steps: Under an inert atmosphere, a mixed solution of calcium source, iron source and silicon source was mixed with a polycarboxylate superplasticizer solution and stirred to react. After the reaction was completed, the mixture was filtered, the precipitate was collected and dried to obtain the novel nanocomposite material.
[0010] Preferably, the stirring reaction takes place for 1 day.
[0011] More preferably, the mixed solution of calcium source and iron source is obtained by mixing equal volumes of 1 mol / L Ca(NO3)2·4H2O aqueous solution and 0.03 mol / L Fe(NO3)3·9H2O aqueous solution.
[0012] More preferably, the silicon source solution is a 1 mol / L Na2SiO3・9H2O aqueous solution.
[0013] More preferably, the preparation method of the polycarboxylate superplasticizer solution includes the following steps: Dissolve tablet polycarboxylate superplasticizer (tablet PCE) in 3 times its weight of deionized water and stir thoroughly for 15 minutes. Then, add NaOH solution dropwise to adjust the pH to 11.8 to obtain the polycarboxylate superplasticizer solution.
[0014] Beneficial effects: The nano-CFSH / PCE in this invention, due to the introduction of iron, can significantly increase the specific surface area and refine the particle size to provide more nucleation sites. When incorporated into cement, it can significantly accelerate the hydration of the silicate phase, forming more CH and CSH products and releasing some free water, but it will significantly shorten the hydration induction period, leading to over-hydration in the early stage.
[0015] Preferably, the auxiliary powder material is obtained by mixing gypsum dihydrate and anhydrous gypsum in a mass ratio of 2:1.
[0016] Beneficial effects: The main function of the auxiliary powder material in this invention is to mitigate the inhibitory / interference effect of rapid hydration of C4AF on C3S during the hydration deceleration period. Dihydrate gypsum has a faster dissolution rate than anhydrous gypsum; when the two are combined in a 2:1 ratio, a continuous and stable release of sulfate ions can be achieved, effectively preventing premature depletion of sulfate in the system and achieving stable control of the hydration process.
[0017] Preferably, the cyclodextrin is β-cyclodextrin.
[0018] Preferably, the sugar is cane molasses.
[0019] Beneficial effects: The cyclodextrin and sugars in this invention can interact with Ca... 2+ The complexation and adsorption of the hydration complexes delay the hydration induction period to a certain extent, avoid structural defects, and reduce the early hydration temperature rise.
[0020] A method for preparing a strengthening agent specifically for low-heat silicate cement includes the following steps: Triolamine, novel nanocomposite material, cyclodextrin and sugar are added to water and stirred to dissolve, thus obtaining the liquid strengthening agent; the raw materials of the auxiliary powder material are mixed evenly to obtain the auxiliary powder material, thereby completing the preparation of the special strengthening agent for low-heat silicate cement.
[0021] Beneficial effects: The auxiliary powder particles pre-mixed uniformly in this invention do not have local enrichment and are evenly distributed in the gaps between cement particles. When the liquid strengthening agent is subsequently added to the cement, the nanocomposite material, triolamine and slow-release components work synergistically to effectively avoid localized excessively rapid hydration and heat concentration, thus taking into account the advantages of strengthening and low heat.
[0022] Application of a special strengthening agent for low-heat silicate cement in low-heat silicate cement.
[0023] Beneficial effects: The incorporation of nano-CFSH / PCE provides more nucleation sites for the ultra-early hydration process of the system, accelerates the early hydration of the silicate phase and promotes the formation of CSH and CH, while cyclodextrin and molasses complex Ca 2+ Adsorption moderately delays the hydration induction period, effectively avoiding early overhydration and structural defects caused by nanomaterials. During the hydration deceleration period, the excellent complexing and solubilizing effect of triolamines on C4AF significantly accelerates C4AF hydration and promotes the formation of AFt and AFm phases. Meanwhile, the 2:1 compounded gypsum (dihydrate for rapid sulfur supply, anhydrous gypsum for continuous sulfur replenishment) provides a stable sulfate supply, ensuring timely rehydration of the aluminate phase while preventing excessive interference of the enhanced C4AF reaction with silicate phase hydration. Ultimately, this achieves significant strength enhancement without increasing the heat of hydration, making it suitable for low-heat silicate cement systems.
[0024] Preferably, the amount of the special strengthening agent added is 0.625wt.%-1.125wt.% of the mass of the low-heat silicate cement.
[0025] Beneficial effects: The dosage selection mainly takes into account the balance between the liquid strengthening agent and sulfate. Lower or higher dosages will not be able to reflect the strength gain effect well.
[0026] Compared with the prior art, the present invention has the following advantages and technical effects: This invention addresses the unique mineral phase composition of low-heat silicate cement (LHPC) by providing an admixture that simultaneously enhances both early and late-stage strength without increasing the heat of hydration. By incorporating novel nanocomposite materials and triolamines, this invention synergistically promotes hydration of LHPC at all ages and improves its strength at low dosages. This is of significant importance for the further promotion and practical application of low-heat silicate cement. Detailed Implementation
[0027] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0028] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to specific embodiments.
[0029] Unless otherwise specified, all raw materials used in the embodiments of this invention were purchased through commercial channels; Among them, the tablet PCE is a tablet polycarboxylate superplasticizer, purchased from Shandong Zhuoxing Chemical Co., Ltd., model SPS-28.
[0030] The mineral phase composition (wt.%) of LHPC is shown in the table below: Unless otherwise specified, room temperature or normal temperature in the embodiments of the present invention refers to 25±3℃.
[0031] Example 1 A strength-enhancing agent for low-heat silicate cement comprises the following raw materials in parts by weight: 10 parts diethanol monoisopropanolamine, 30 parts nano CFSH / PCE, 25 parts auxiliary powder material (a mixture of dihydrate gypsum and anhydrous gypsum in a mass ratio of 2:1), 5 parts β-cyclodextrin, 5 parts sugarcane molasses, and 25 parts deionized water.
[0032] A method for preparing a strengthening agent specifically for low-heat silicate cement includes the following steps: 1) Preparation of nano-CFSH / PCE: (1) Preparation of reaction solution: (1-1) Dissolve the tablet PCE in 3 times the mass of deionized water and stir thoroughly for 15 minutes. Pour the solution into a reaction vessel and then use a high-precision peristaltic pump tube to add 0.8 mol / L NaOH solution to adjust the pH to 11.8. Place the solution in a water bath at a constant temperature of 25°C as the reaction base solution.
[0033] (1-2) Prepare a 1 mol / L Ca(NO3)2·4H2O aqueous solution in a volumetric flask as a calcium source solution; prepare a 0.03 mol / L Fe(NO3)3·9H2O aqueous solution in a volumetric flask as an iron source solution. Take 100 mL of each calcium source solution and iron source solution, stir and mix them, and place them in an Erlenmeyer flask to obtain solution A.
[0034] (1-3) Prepare a 1 mol / L Na2SiO3·9H2O aqueous solution in a volumetric flask as the silicon source solution (solution B). Take 100 mL of solution B and place it in an Erlenmeyer flask.
[0035] (2) Using a high-precision peristaltic pump tube, solutions A and B were simultaneously added dropwise to the base liquid over a period of 1 hour. The stirring speed was 500 rpm, and nitrogen gas was introduced throughout the process to prevent carbonization. After the addition was completed, the mixture was stirred continuously at 25°C for 1 day to ensure a complete reaction. Finally, vacuum filtration was performed to separate the solid and liquid phases and collect the precipitate. The precipitate was then dried in a vacuum oven at 30°C and a vacuum degree of 0.05 MPa to obtain nano-CFSH / PCE.
[0036] 2) Preparation of a special strengthening agent for low-heat silicate cement: According to the above-mentioned raw material addition amounts, deionized water was added to the stirred tank, followed by diethanol monoisopropanolamine, nano-CFSH / PCE, β-cyclodextrin, and cane molasses. The mixture was stirred for 20 minutes and allowed to stand to obtain a liquid strengthening agent. The uniformly mixed auxiliary powder materials were placed separately.
[0037] Example 2 A strength-enhancing agent for low-heat silicate cement comprises the following raw materials in parts by weight: 10 parts triisopropanolamine, 30 parts nano CFSH / PCE, 25 parts auxiliary powder material (a mixture of dihydrate gypsum and anhydrous gypsum in a mass ratio of 2:1), 5 parts β-cyclodextrin, 5 parts cane molasses, and 25 parts deionized water.
[0038] A method for preparing a low-heat silicate cement strengthening agent is the same as in Example 1. Example 3 A strength-enhancing agent for low-heat silicate cement comprises the following raw materials in parts by weight: 10 parts diethanol monoisopropanolamine, 30 parts nano CFSH / PCE, 30 parts auxiliary powder material (a mixture of dihydrate gypsum and anhydrous gypsum in a mass ratio of 2:1), 5 parts β-cyclodextrin, 5 parts sugarcane molasses, and 20 parts deionized water.
[0039] A method for preparing a strengthening agent specifically for low-heat silicate cement includes the following steps: 1) Preparation of nano-CFSH / PCE: (1) Preparation of reaction solution: (1-1) Dissolve the tablet PCE in 3 times the mass of deionized water and stir thoroughly for 15.0 min. Pour into a reaction vessel, then use a high-precision peristaltic pump tube to add 0.8 mol / L NaOH solution to adjust the pH to 11.8. Place in a water bath at a constant temperature of 25℃ as the reaction base solution.
[0040] (1-2) Prepare a 1 mol / L Ca(NO3)2·4H2O aqueous solution in a volumetric flask as a calcium source solution; prepare a 0.03 mol / L Fe(NO3)3·9H2O aqueous solution in a volumetric flask as an iron source solution. Take 100 mL of each calcium source solution and iron source solution, stir and mix them, and place them in an Erlenmeyer flask to obtain solution A.
[0041] (1-3) Prepare a 1 mol / L Na2SiO3·9H2O aqueous solution in a volumetric flask as the silicon source solution (solution B). Take 100 mL of solution B and place it in an Erlenmeyer flask.
[0042] (2) Using a high-precision peristaltic pump tube, solutions A and B were simultaneously added dropwise to the base liquid over a period of 1 hour. The stirring speed was 500 rpm, and nitrogen gas was introduced throughout the process to prevent carbonization. After the addition was completed, the mixture was stirred continuously at 25°C for 1 day to ensure a complete reaction. Finally, vacuum filtration was performed to separate the solid and liquid phases and collect the precipitate. The precipitate was then dried in a vacuum oven at 30°C and a vacuum degree of 0.05 MPa to obtain nano-CFSH / PCE.
[0043] 2) Preparation of a special strengthening agent for low-heat silicate cement: According to the above-mentioned raw material addition amounts, deionized water was added to the stirred tank, followed by diethanol monoisopropanolamine, nano-CFSH / PCE, β-cyclodextrin, and cane molasses. The mixture was stirred for 20 minutes and allowed to stand to obtain a liquid strengthening agent. The uniformly mixed auxiliary powder materials were placed separately.
[0044] Example 4 A strength-enhancing agent for low-heat silicate cement comprises the following raw materials in parts by weight: 15 parts diethanol monoisopropanolamine, 25 parts nano CFSH / PCE, 25 parts auxiliary powder material (a mixture of dihydrate gypsum and anhydrous gypsum in a mass ratio of 2:1), 5 parts β-cyclodextrin, 5 parts sugarcane molasses, and 25 parts deionized water.
[0045] The preparation method of a low-heat silicate cement strengthening agent is the same as that in Example 1.
[0046] Example 5 A strength-enhancing agent for low-heat silicate cement comprises the following raw materials in parts by weight: 15 parts diethanol monoisopropanolamine, 35 parts nano CFSH / PCE, 30 parts auxiliary powder material (a mixture of dihydrate gypsum and anhydrous gypsum in a mass ratio of 2:1), 5 parts β-cyclodextrin, 5 parts sugarcane molasses, and 10 parts deionized water.
[0047] The preparation method of a low-heat silicate cement strengthening agent is the same as that in Example 1.
[0048] Example 6 A strength-enhancing agent for low-heat silicate cement comprises the following raw materials in parts by weight: 10 parts diethanol monoisopropanolamine, 35 parts nano CFSH / PCE, 30 parts auxiliary powder material (a mixture of dihydrate gypsum and anhydrous gypsum in a mass ratio of 2:1), 5 parts β-cyclodextrin, 5 parts sugarcane molasses, and 30 parts deionized water.
[0049] The preparation method of a low-heat silicate cement strengthening agent is the same as that in Example 1.
[0050] Example 7 A strength-enhancing agent for low-heat silicate cement comprises the following raw materials in parts by weight: 15 parts diethanol monoisopropanolamine, 25 parts nano CFSH / PCE, 30 parts auxiliary powder material (a mixture of dihydrate gypsum and anhydrous gypsum in a mass ratio of 2:1), 5 parts β-cyclodextrin, 5 parts sugarcane molasses, and 20 parts deionized water.
[0051] The preparation method of a low-heat silicate cement strengthening agent is the same as that in Example 1.
[0052] Comparative Example 1 The only difference from Example 1 is that nano-CFSH / PCE is replaced with nano-CSH, specifically comprising the following parts by weight of raw materials: 10 parts diethanol monoisopropanolamine, 30 parts nano CSH, 25 parts auxiliary powder material (a mixture of dihydrate gypsum and anhydrous gypsum in a mass ratio of 2:1), 5 parts β-cyclodextrin, 5 parts sugarcane molasses, and 25 parts deionized water.
[0053] Includes the following steps: 1) Preparation of nano-CSH: (1-1) Take 0.7g NaOH, add 200mL of deionized water, mix well, pour into the reaction vessel, at which point the pH is 13.0, and place it in a constant temperature water bath at 25℃ as the reaction base liquid.
[0054] (1-2) Prepare a 0.1 mol / L Na₂SiO₃ solution as the silicon source solution (solution A) using a volumetric flask, and prepare a 0.12 mol / L CaCl₂ solution (solution B) as the calcium source solution. Take 100 mL of each solution and place them in a conical flask.
[0055] (1-3) Using a high-precision peristaltic pump tube, solutions A and B were simultaneously added dropwise to the base liquid over a period of 1 hour. The stirring speed was 200 rpm, and nitrogen gas was introduced throughout the process to prevent carbonization. After the addition was complete, the mixture was stirred continuously at 25°C for 1 day to ensure a complete reaction. Finally, vacuum filtration was performed to separate the solid and liquid phases and collect the precipitate. The precipitate was then dried in a vacuum oven at 30°C and a vacuum degree of 0.05 MPa to obtain nano-CSH.
[0056] 2) Preparation of a special strengthening agent for low-heat silicate cement: According to the above-mentioned raw material addition amounts, deionized water was added to the mixing tank, followed by diethanol monoisopropanolamine, nano-CSH, β-cyclodextrin, and cane molasses. The mixture was stirred for 20 minutes and allowed to stand to obtain a liquid strengthening agent. The uniformly mixed auxiliary powder materials were placed separately.
[0057] Comparative Example 2 The only difference from Example 1 is that diethanol monoisopropanolamine is replaced with monoethanol diisopropanolamine, specifically comprising the following raw materials in parts by weight: 10 parts monoethanol diisopropanolamine, 30 parts nano CFSH / PCE, 25 parts auxiliary powder material (a mixture of dihydrate gypsum and anhydrous gypsum in a mass ratio of 2:1), 5 parts β-cyclodextrin, 5 parts sugarcane molasses, and 25 parts deionized water.
[0058] The preparation method is the same as in Example 1.
[0059] Comparative Example 3 The only difference from Example 1 is that it does not include auxiliary powder materials, and specifically includes the following raw materials in parts by weight: 10 parts diethanol monoisopropanolamine, 30 parts nano CFSH / PCE, 5 parts β-cyclodextrin, 5 parts cane molasses, and 25 parts deionized water.
[0060] The preparation method is the same as in Example 1.
[0061] Technical effects: 1. Heat release and mechanical properties The strengthening agents obtained in Examples 1-7 and Comparative Examples 1-3 were added to low-heat silicate cement (LHPC) respectively (the total amount of strengthening agent added was 0.625 wt.% of the cement mass). The addition method was as follows: first, the auxiliary powder material and cement were mixed evenly, and then the liquid strengthening agent was added. After mixing evenly with a water-cement ratio of 0.5, cement paste was obtained.
[0062] The cumulative heat release of cement paste (W / C=0.5) over 3 days was tested using a TAM-AIR isothermal calorimeter at 20℃. The cement mortar strength was determined after curing according to GB / T 17671-1999 "Test Method for Strength of Cement Mortar (ISO Method)". LHPC without strengthening agent was used as a control (blank group). The cumulative heat release results for 1 day and 3 days are shown in Table 1, and the compressive strength comparison results are shown in Table 2.
[0063] Table 1. Cumulative heat release over 1 day and 3 days Table 2 Comparison of compressive strength before and after the addition of the strengthening agent As shown in Tables 1 and 2, all seven examples increased the compressive strength of LHPC at 1d, 3d, and 28d. Overall, Example 1 showed the best effect, with compressive strengths at 1d, 3d, and 28d increasing by 3.8 MPa, 2.8 MPa, and 3.7 MPa compared to the control group, respectively. Furthermore, Comparative Example 3 showed a disadvantage in that the heat release at 1d and 3d was significantly higher without the addition of auxiliary powder materials. In Comparative Example 2, the effect of monoethanol diisopropanolamine was less than that of diethanol monoisopropanolamine, and the effect at 3d was significantly lower than that of Example 1. In Comparative Example 1, the reinforcing and dispersing effects of nano-CSH were inferior to those of nano-CFSH, and its effect at 1d was significantly lower than that of Example 1.
[0064] 2. Effect of strengthening agent dosage on early heat release and compressive strength The strengthening agent prepared in Example 1 of this invention (with dosages of 0.875 wt.%, 1 wt.%, and 1.125 wt.% of the cement mass, respectively) was added to LHPC. Then, water was added to control the water-cement ratio at 0.5, and the mixture was stirred evenly to obtain a slurry. The cumulative heat release of the slurry (W / C=0.5) over 3 days was tested using a TAM-AIR isothermal calorimeter at 20°C. The results are shown in Table 3.
[0065] Table 3 As can be seen from Table 3, the dosage of the strengthening agent has a significant effect on the early heat release and strength. When the dosage is increased, the cumulative heat release and strength over 3 days are significantly reduced. This is because the rehydration of C4AF caused by alkanolamine is significantly delayed in the presence of a higher content of sulfate carrier, which inhibits the formation of products such as ettringite, monosulfide hydrated calcium sulfoaluminate, and calcium hydroxide in this stage.
[0066] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A strengthening agent specifically for low-heat silicate cement, characterized in that, Including liquid strengthening agents and auxiliary powder materials; The mass ratio of the liquid reinforcing agent to the auxiliary powder material is (55-90):(25-30); The liquid strengthening agent comprises the following raw materials in parts by weight: 10-15 parts of triolamine, 25-35 parts of novel nanocomposite material, 5 parts of cyclodextrin, 5 parts of sugar, and 10-30 parts of water.
2. The low-heat silicate cement strengthening agent according to claim 1, characterized in that, The triolamine includes triisopropanolamine or diethanol monoisopropanolamine.
3. The low-heat silicate cement strengthening agent according to claim 1, characterized in that, The novel nanocomposite material is a nano-hydrated iron calcium silicate / polycarboxylate superplasticizer material.
4. The low-heat silicate cement strengthening agent according to claim 3, characterized in that, The preparation method of the novel nanocomposite material includes the following steps: Under an inert atmosphere, a mixed solution of calcium source, iron source and silicon source was mixed with a polycarboxylate superplasticizer solution and stirred to react. After the reaction was completed, the mixture was filtered, the precipitate was collected and dried to obtain the novel nanocomposite material.
5. The low-heat silicate cement strengthening agent according to claim 4, characterized in that, The stirring reaction was carried out over a period of 1 day.
6. The low-heat silicate cement strengthening agent according to claim 1, characterized in that, The auxiliary powder material is obtained by mixing dihydrate gypsum and anhydrous gypsum in a mass ratio of 2:
1.
7. The low-heat silicate cement strengthening agent according to claim 1, characterized in that, The sugar is sugarcane molasses.
8. A method for preparing a low-heat silicate cement strengthening agent as described in any one of claims 1-7, characterized in that, Includes the following steps: Triolamine, novel nanocomposite material, cyclodextrin and sugar are added to water and stirred to dissolve, thus obtaining the liquid strengthening agent; the raw materials of the auxiliary powder material are mixed evenly to obtain the auxiliary powder material, thereby completing the preparation of the special strengthening agent for low-heat silicate cement.
9. The application of a low-heat silicate cement strengthening agent as described in any one of claims 1-7 in low-heat silicate cement.
10. The application according to claim 9, characterized in that, The dosage of the special strengthening agent is 0.625wt.%-1.125wt.% of the mass of low-heat silicate cement.